รูปแบบความสัมพันธ์เชิงสาเหตุของทฤษฎีรวมการยอมรับและการใช้เทคโนโลยีที่มีผลต่อพฤติกรรมการสื่อสารภายในองค์กรผ่านโซเชียลมีเดียของข้าราชการโรงเรียน เตรียมทหาร สถาบันวิชาการป้องกันประเทศ CASUAL RELATIONSHIP MODEL OF UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY ON COMMUNICATION BEHAVIOR IN ORGANIZATION THROUGH SOCIAL MEDIA OF ARMED FORCES ACADEMIES PREPARATORY SCHOOL - เกิดสวัสดิ์ ศุภสัณห์; ปานคำ สุมามาลย์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2021)
This research aimed to develop the causal relationship model of unified theory of acceptance and use of technology on communication behavior in organizations through social media and verify the conformity of the causal relationship model that has been developed with empirical data. The sample group in this research included 400 officers of Armed forces academies preparatory school. That used the LINE application for internal communication, selected by using the simple sampling method. A questionnaire composed of the 7 scale, with reliability at 0.97, was applied to collect the data. The data were analysis by structural equation modeling. The findings were as follows: the causal relationship model of unified theory acceptance and use of technology on communication behavior in organizations through social media consists of six factors, as follows: Explanatory Variable, which were Performance Expectancy for Social Media, Effort Expectancy of using Social Media, Social Influence toward the use of Social Media, Facilitating Conditions the use of Social Media. Mediator Variable, which were Behavioral Intention of using Social Media and Dependent Variable, which were Use Behavior of using Social Media for Internal Communication. The findings were as follows: the causal relationship model that has been developed conformed to the empirical data to a great extent. From statistic shows the Chi-square = 230.86, degrees of freedom = 117, CMIN/DF = 1.97, RMR – 0.04, RMSEA = 0.04 and index Value AGFI, GFI, CFI, IFI, TLI = 0.91, 0.94, 0.98, 0.98, 0.97. By Behavioral Intention of using Social Media has influences and Facilitating Conditions the use of Social Media to Use Behavior of using Social Media for Internal Communication.